Logistics decisions in the installation of offshore wind farms: framework proposal - Nascimento, Gabriela Soares do (2021)
Logistics influences production and distribution costs and time in several sectors. In the offshore wind energy sector, installation logistics costs can reach 20% of CAPEX. Two relevant factors in the sector are: the accelerated technological development, with an increase in the rated power and in the dimensions of the turbines; and the increased distance from the offshore wind farms to the coast, these influence the costs of installing offshore wind farms. The study aims to propose a framework for logistical decisions for the installation of offshore wind farms. The research method is characterized as descriptive, with a qualitative-quantitative approach. The research procedure included theoretical research on offshore wind energy, installation of offshore wind farms and logistics, using systematic literature review. The field research consisted of a survey with 29 experts from 14 different countries to validate the conceptual framework. As a result, the framework contemplates 8 logistical decisions required in the installation of an offshore wind farm that impact “time” and “cost” performance objectives. Logistics decisions are influenced by factors: environmental and meteorological conditions, project characteristics, turbine characteristics, characteristics of available vessels, availability of infrastructure for installation logistics and stakeholders. Finally, it is concluded that the proposed framework presents the importance of decision making with a global view, highlighting that taking only one decision not combined with the others can harm and increase the costs of the next decision.